2014
DOI: 10.1016/j.tranon.2014.09.010
|View full text |Cite
|
Sign up to set email alerts
|

New Approach for Interpreting Changes in Circulating Tumour Cells (CTC) for Evaluation of Treatment Effect in Metastatic Breast Cancer

Abstract: Aim: Attempts have been made to use CTC values for interpretation of treatment response and to guide change of chemotherapy by using a static cut-off of 5 CTC to stratify patients in favourable or unfavourable responders. We propose a new approach to interpret treatment effect using significant changes in CTC values (SCV-limits1) as grouping parameter for responders and non-responders to chemotherapy among metastatic breast cancer (mBC) patients. Method: CTC were analysed using the CellSearch System in blood f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Finally, 50 studies were eligible for meta-analysis (Fig. 1)4591112131415161718192021222324252627282930313233343536373839404142434445464748495051525354555657.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 50 studies were eligible for meta-analysis (Fig. 1)4591112131415161718192021222324252627282930313233343536373839404142434445464748495051525354555657.…”
Section: Resultsmentioning
confidence: 99%
“…The data also pointed to a better prognosis for patients in whom CTC-status became negative after therapy, but this was less convincing, especially for PFS. Horn et al demonstrated the prognostic relevance of a significant change value of the CTC count between baseline and three therapy cycles to define a CTC evaluation method for the low and medium risk groups [35]. This method allows to also take initially CTC negative patients into account for CTC decrease.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 Enrichment, detection and counting of CTCs is very important because it allows for statistical predictions concerning the overall survival time and the response of patients to anticancer therapies. 6 While enrichment and counting is already a big step forward, molecular information and how the cells will respond to therapeutic efforts is still locked away inside them. Consequently, to obtain this information, a prerequisite for any personalized cancer drugs that target selected pathways, analytical downstream processes after cell isolation are needed.…”
mentioning
confidence: 99%
“…Thus, information on the extent of the circulation of these cells is of great interest, especially at early stages in tumor development. CTC invasion into the blood can occur during any stage of tumor development, but it might even be provoked by diagnostic or therapeutic procedures (e.g., palpation, biopsy, surgery, drugs). , Enrichment, detection and counting of CTCs is very important because it allows for statistical predictions concerning the overall survival time and the response of patients to anticancer therapies . While enrichment and counting is already a big step forward, molecular information and how the cells will respond to therapeutic efforts is still locked away inside them.…”
mentioning
confidence: 99%